The theory and practice of technology in materials development and task design - Reinders H; White CJ (Cambridge University Press, 2010)
Technology nowadays plays a prominent role in the development of language learning materials, both as a tool in support of their creation and as a means of delivering content. Increasingly, technology is also used to support the individual’s language learning process and to extend language learning opportunities outside the classroom. The development of materials is still largely a practitioner-led practice, not always clearly informed by theories of learning (Chapelle 2001). In this chapter we aim to firstly identify the distinctive features of computer-assisted language learning (CALL) materials versus traditional non-CALL materials, and how these features affect their development. Theoretical principles for task design in CALL are reviewed followed by examples of current practice in CALL materials development discussed from a practical, pedagogical, and a theoretical perspective. We conclude by identifying a number of issues that are likely to affect future developments in this area.
Keywords: Fields of Research::420000 Language and Culture::420100 Language Studies